Evaluation of antioxidant activity of phenolic fractions from the leaves and petals of dandelion in human plasma treated with H2O2 and H2O2/Fe. (25th January 2017) - Jędrejek, Dariusz; Kontek, Bogdan; Lis, Bernadetta; Stochmal, Anna; Olas, Beata
Abstract: Taraxacum officinale (dandelion) is a widespread perennial of the Asteraceae family. Dandelion is a rich source of different bioactive compounds, including phenolic compounds, terpenes, carbohydrates, proteins, fatty acids, vitamin and minerals. However, the content of phenolics in tested extracts by various authors was not always well described. Dandelion is also a commonly available food with a long history of human use and as such poses little risk of harm. In this study, we focused on four different phenolic fractions from leaves and petals of dandelion, which might be of great interest. The objective was to investigate the antioxidant properties of the phenolic fractions from dandelion leaves and petals in vitro . Effects of four different phenolic fractions from dandelion leaves and petals on the production of thiobarbituric acid reactive substances (TBARS, a marker of lipid peroxidation) in human plasma were studied in vitro . Their antioxidant properties against human plasma protein carbonylation and oxidation of protein thiols induced by a strong biological oxidant – hydrogen peroxide (H2 O2 ) or H2 O2 /Fe (a donor of hydroxyl radicals) were also examined. The tested fractions of dandelion (0.5–50 μg/mL; the incubation time – 30 min) inhibited plasma lipid peroxidation induced by H2 O2 or H2 O2 /Fe. However, their antioxidant properties were not concentration-dependent. All tested samples also inhibited plasma protein carbonylation and oxidation of thiol groups in plasma proteins stimulated by oxidants (H2 O2 and OH ∙ ). The obtained results suggest that four tested dandelion fractions, especially phenolic fractions from petals which are recognized as better than leaves source of flavonoids, may be a new and promising source of natural compounds with antioxidant activity beneficial for diseases-associated with oxidative stress, and with changes of hemostasis. Highlights: Four different phenolic fractions from T. officinale leaves and petals were analyzed. All tested fractions from T. officinale leaves and petals had antioxidative properties. They inhibited lipid peroxidation, protein carbonylation and oxidation of protein thiols. Fractions from petals had stronger antioxidant activity than fractions from leaves. Tested dandelion fractions may be a promising source of antioxidants.